Trisutji Kamal’s Loro Jonggrang: A Cross-Cultural Dissonance - Marusya Nainggolan; Melani Budianta; Nyak Ina Raseuki; Harsawibawa (Wacana Seni Journal of Arts Discourse, 2022)
Trisutji Kamal, whose career spanned five decades, was one of the oldest and longest-performing Indonesian female classical composers. Her music is tinged with a unique character, stemming from the way she inserted Javanese nuances into the Western framework of her art. To discuss this musical style, the authors analysed one of her most well-known compositions in the form of an opera, called Loro Jonggrang. The article examines how the two different musical traditions from the West and Java intersect in her music and her cultural subjectivity. The authors argue that what emerges in her music is a sense of dissonance through the use of pseudo pentatonic, two chords, drone, accents, and beats, connecting Trisutji’s music with her cultural background and life history. The authors contend that the dissonant turn and glissando effect of her music comes from the tension between Western musical forms and Javanese intuition. The article contributes to the rare scholarship about female composers in Southeast Asia.